The Impact of Social Media Use: A Case Study of Verbal Bullying on Adolescents - Dilla Amalia Muntaha; Ario Mukti Lazuardi Anggomulyo; Muhammad Aras (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Adolescence is a period of transition from children to adults, so at this time the search for identity becomes one of the needs to understand oneself and show oneself to others. In the development of technology, the majority of teenagers use social media. This study aims to determine the impact of using social media in case studies of verbal bullying that occur among adolescents. This type of research is a case study research with a qualitative approach. Respondents in this study were social media users, especially teenagers. Data collection techniques using interviews, observations and documents. The data analysis technique uses research data processing by listening, selecting data, analyzing data, analyzing data and concluding results. The results of this study are that the existence of social media has influenced social life in society, one of which has an impact on verbal bullying behavior. Verbal bullying is bullying/bullying that is conveyed verbally, which can take the form of criticizing, shouting, insulting, nicknames, spreading gossip/slander, dropping criticism, invitations and expressions that lead to sexual harassment, and so on and this bullying is the most common. . Parental and peer support helps adolescents to cope with bullying by focusing on developing adolescent interests.